From preferences between arguments to preferences between explanations - Burrieza-Muñiz, Alfredo; Yuste-Ginel, Antonio (My University, 2018)
In this ongoing work we present a new approach to the problem of argument evaluation. According to our view the notion of preference between deductive arguments is reducible to simpler notions. Departuring from this analysis we intend to apply it to the problem of hypothesis selection in explanatory practices.
Keywords: Lógica epistémica; Epistemic logic; Justifications; Abduction; Preferences; Arguments